Robert Ludlum's The Bourne imperative : a new Jason Bourne novel - Lustbader, Eric Van; Ludlum, Robert (London : Orion Books, 2012)
After retrieving a nearly-dead gunshot victim from beneath a frozen lake, Jason Bourne must help the injured man regain his memory and find out who did this to him.
Keywords: Intelligence officers; Amnesia; Conspiracies; Terrorists; Memory; Betrayal